2018
DOI: 10.1111/1365-2435.13193
|View full text |Cite
|
Sign up to set email alerts
|

Fire increases drought vulnerability of Quercus alba juveniles by altering forest microclimate and nitrogen availability

Abstract: Shifts in rainfall patterns due to climate change are expected to increase drought stress and mortality in forests. Natural and anthropogenic fire regimes are also changing, highlighting the need to understand the interactive effects of fire and drought on tree ecophysiological response and growth. Using rainout shelters, we imposed summer drought on natural and planted populations of Quercus alba juveniles located in periodically burned and unburned sites in Shawnee National Forest, IL, USA. A subset of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Prescribed fire shifts forest microclimate toward a greater frequency of temperature and humidity conditions known to limit tick success and survival. Mechanistically, reductions in canopy and understory density and the creation of gap space from prescribed burning increase solar exposure (Stevens, 2017), reduce evapotranspiration (Clark et al, 2012), and increase understory wind speed (Ma et al, 2010), promoting hotter and drier understory conditions during the daytime (Iverson & Hutchinson, 2002; Refsland & Fraterrigo, 2018) and colder temperatures at night. This enhances diurnal temperature fluctuations and enables a higher frequency of moisture and temperature extremes relative to tick tolerances for behavior, development time, molting success, and overall survival (Schulze et al, 2001; Vail & Smith, 1998).…”
Section: Prescribed Fire As a Control For Tick Populationsmentioning
confidence: 99%
“…Prescribed fire shifts forest microclimate toward a greater frequency of temperature and humidity conditions known to limit tick success and survival. Mechanistically, reductions in canopy and understory density and the creation of gap space from prescribed burning increase solar exposure (Stevens, 2017), reduce evapotranspiration (Clark et al, 2012), and increase understory wind speed (Ma et al, 2010), promoting hotter and drier understory conditions during the daytime (Iverson & Hutchinson, 2002; Refsland & Fraterrigo, 2018) and colder temperatures at night. This enhances diurnal temperature fluctuations and enables a higher frequency of moisture and temperature extremes relative to tick tolerances for behavior, development time, molting success, and overall survival (Schulze et al, 2001; Vail & Smith, 1998).…”
Section: Prescribed Fire As a Control For Tick Populationsmentioning
confidence: 99%
“…The sensitivity of different species to wildfires may be very different, and secondary hazards may occur after a fire, thus it is often difficult to determine if the death of certain organism is caused by wildfire or the result of ecosystem response. The cause of tree death can be complex, and many factors can lead to misjudgment; for example, bark beetles that are not easy to detect spread quickly after forest fire (Ray et al 2019;Stevens-Rumann et al 2015), changes in soil physical and chemical properties after wildfires (Holden et al 2016;Ludwig et al 2018;Quintero-Gradilla et al 2015), and changes of microclimate after forest fires (Refsland and Fraterrigo 2018;Watts and Kobziar 2015).…”
Section: Quantifying Fire Severity By Vegetation Changementioning
confidence: 99%
“…In addition to the negative impact on seedling recruitment, drought can also affect the regeneration of burned areas thought the increase in the vulnerability of resprouting plants (Pratt et al, ). In fact, although it was already shown that resprouting species often display a better water status in the months after the crown fire (probably due to reduced leaf area and thus higher root‐to‐shoot ratio; Clemente, Rego, & Correia, ; Ramirez, Pratt, Jacobsen, & Davis, ; Refsland & Fraterrigo, ; Schwilk, Brown, Lackey, & Willms, ), they tend to be more vulnerable to drought than co‐occurring unburned plants (Ramirez et al, ; Saruwatari & Davis, ). An example of the higher vulnerability of resprouting plants is the well‐documented increase in mortality rates of shrub species from a chaparral community when intense drought occurred in the following year after a fire event (Pratt et al, ).…”
Section: Main Drivers Of Forest Dieback Under a Scenario Of Climate Cmentioning
confidence: 99%